Implikasi Penataan Desa Wisata Penglipuran terhadap Kelestarian Budaya Bali - A.A. Putu Bayu Surya Dharma Gede; Gede Yoga Kharisma Pradana2 (Sekolah Tinggi Pariwisata Sahid Surakarta, 2022)
The purpose of this publication is to report the results of revealing the relationship between the Penglipuran tourist village and the Balinese culture. Penglipuran known as the tourist village with the best arrangement due to national and international awards. The success of the Penglipuran tourism village arrangement cannot be separated from the role of the Balinese people. The questions are: 1) What is the shape of the Penglipuran Tourism Village arrangement? 2) Does the arrangement of the Penglipuran tourist village have an impact on the preservation of Balinese culture?. This article was written using a qualitative method from the perspective of the sociology of tourism. The primary data required is descriptive, so this qualitative method was chosen. The article production process is optimized by using an ethnomethodological approach and a positivistic paradigm. Some of the data was collected through observation and interviews. Some of the information was obtained through library research. The structural functional and symbolic theory were used to analyze all data qualitatively. The results expected to contribute academically to researchers who are conducting research on tourist villages and Balinese culture. The results of the study show that: 1) Penglipuran tourism village, which is managed for tourists, is in the form of a community-based tourism village; 2) The arrangement of the Penglipuran tourist village has an indirect impact on the preservation of Balinese culture in accordance with local customs. Through the Penglipuran Tourism Village, it is very possible to preserve Balinese culture in the local community.